PENGARUH IMAGERY TRAINING TERHADAP KETEPATAN DALAM MELAKUKAN SHOOTING DALAM PERMAINAN FUTSAL - Supiyanto Supiyanto; Victor G Simanjuntak; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract       The problem in this research is, the low ability of athletes in shooting in futsal games, is there any influence of imagery training methods on the accuracy of shooting in Futsal games in Princess Futsal UKM IKOR Tanjungpura University Pontianak.The method in this study uses the method of experimental form Pre-Experimental with One-Group Pretest-posttest design. The population in this study were 14 female students of Princess IKOR Futsal University in Tanjungpura Pontiana. Samples taken from the results of purposive sampling, with the criteria that is; (1) Students studying at FKIP Physical Education, Tanjungpura University, Pontianak. (2) still active and following  futsal training. (3) attending 12 sessions of training. (4) Female sex. Based on these criteria, those who meet are 14 people. The instrument used to test the accuracy of shooting. Data analysis using t test analysis (influence test). Based on the calculation of data obtained (shooting) with an average pretest result of 3.07 and posttest of 5.71. Increased by 2.69 Then the t-test was calculated to get the t count in the imagery training method is 11.42 and the t table was 1.771 and the significance level of 5% with t count> t table. So it can be said that Ho is rejected and Ha is accepted, meaning that there is an influence of imagery training methods on the accuracy (shooting) with a percentage increase of 8,599%.Keywords: Imagery Training Method, Shooting Accuracy.